Nature and Genesis of the Xiaobeigou Fluorite Deposit, Inner Mongolia, Northeast China: Evidence from Fluid Inclusions and Stable Isotopes. Issue 2 (15th October 2018) - Pei, Qiuming; Zhang, Shouting; Hayashi, Ken‐ichiro; Wang, Liang; Cao, Huawen; Zhao, Yu; Hu, Xinkai; Song, Kairui; Chao, Weiwei
Abstract: The recently discovered Xiaobeigou fluorite deposit is situated in the southern part of the Southern Great Xing'an Range metallogenic belt. Fluorite‐bearing veins are rather common over the whole area. So far, 11 mineralized veins have been delineated at the Xiaobeigou deposit. Orebodies of the deposit are mainly hosted in Permian and Jurassic volcano‐sedimentary rocks. The orebodies in this mining district exhibit a well‐developed vertical zonation: from top to bottom, the orebodies can be divided into upper, central, and lower zones. The central zone is the most important part for mining operations, and it shows lateral zonation of fluorite mineralization. Rare earth element (REE) contents of the investigated samples are relatively low (less than 30.2 ppm). Furthermore, the REE contents of the fluorite grains from early to late ore stages exhibit a decreasing trend. All the fluorite samples show no or slightly positive Eu anomalies. Three types of fluid inclusions (FIs) are distinguished in the quartz and fluorite samples, including pure‐liquid single‐phase (PL‐type), liquid‐rich two‐phase (L‐Type), and vapor‐rich two‐phase (V‐type) FIs. The FIs hosted in early‐stage quartz were homogenized at 159.5–260.7°C (mainly 160–240°C); their salinities range from 0.18 to 1.22 wt.% NaCl eqv. The FIs hosted in early‐stage fluorite yield slightly lower homogenization temperatures of 144.4–266.8°C (peaking at 140–220°C), which correspond to salinities of 0.18–0.88 wt.% NaCl eqv. Homogenization temperatures and salinities for the late stage are 132.5–245.8°C (mainly 160–180°C) and 0.18–1.40 wt.% NaCl eqv., respectively. Laser Raman spectroscopy of FIs shows that both the vapor and liquid compositions of the inclusions are dominated by H2 O. The H–O isotopic compositions at Xiaobeigou suggest that the ore‐forming fluids are predominantly of meteoric water origin. The Xiaobeigou deposit can be classified as a typical low‐temperature hydrothermal vein‐type fluorite deposit. Combined with regional data, we infer that the fluorite mineralization occurred during the Late Mesozoic in an extensional setting. Abstract : The newly discovered Xiaobeigou deposit is fault‐controlled and can be classified as a typical low temperature vein‐type fluorite deposit. The orebodies in this mining district exhibit a well‐developed vertical zonation. The ore‐forming fluids may have been derived from an H2O–NaCl system with low temperature, low salinity, and low density and predominantly originated from meteoric water.